Joint trade-off optimization algorithm based on cooperative spectrum sensing throughput - Guo-qing JI; Gang WANG; Hong-bo ZHU (Tongxin xuebao)
The achievable data throughput of the cognitive network was modeled to optimize the overhead and performance of the cooperative system thoroughly.Considering the soft data combination decision,the joint trade-off optimization of the local sampling number and cooperative user number was modeled based on the achievable data throughput.The global optimal solution was achieved with inexact line search algorithm,which is based on Armijo rule and lopsided search step technique.Consequently,the validity of the optimization model was verified both by the numerical computation and by Monte-Carlo simulation tests.The joint trade-off optimization of the sampling number and cooperative user number was achieved in cooperative sensing based on the throughput maximizing criterion.